INSTRUMEN ACADEMIC FLOW DALAM PEMBELAJARAN MATEMATIKA DI SEKOLAH DASAR: VALIDATION AND RELIABILITY TESTING - Rahmawati, Resi; Karlimah; Muhammad Hamzah, Rifqy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop and validate an academic flow instrument in elementary school mathematics learning. The instrument was constructed based on Csikszentmihalyi’s flow theory, which includes the aspects of absorption, enjoyment, and intrinsic motivation. The initial instrument consisted of 30 items administered to 30 sixth-grade students. Validity analysis was conducted using the Rasch model with the assistance of Winstep software, while reliability was tested using Cronbach’s Alpha coefficient. The results of the analysis showed that 6 items did not meet the validity criteria and were therefore removed. The final instrument consisted of 24 valid items. Reliability testing yielded a Cronbach’s Alpha value of 0.81, indicating that the internal consistency of the instrument was in the good category.Thus, the developed academic flow instrument proved to be valid and reliable, and is suitable for assessing the extent to which students experience flow in mathematics learning at the elementary school level. This instrument is expected to assist teachers in designing more effective and engaging learning strategies, as well as provide a foundation for further research on the relationship between flow and other variables in education.